The Enhancement of Neutral Metal Na Layer Above Thunderstorms. Issue 19 (14th October 2017) - Yu, Bingkun; Xue, Xianghui; Lu, Gaopeng; Kuo, Cheng‐Ling; Dou, Xiankang; Gao, Qi; Qie, Xiushu; Wu, Jianfei; Qiu, Shican; Chi, Yutian; Tang, Yihuan
Abstract: Atomic sodium (Na) is one of the major meteoric species existing as layers of atoms in the mesosphere/lower thermosphere (MLT) at altitudes of 80–105 km and atomic ions at higher altitudes. As the boundary between neutral atmosphere and ionosphere, the MLT region is of particular interest because it is influenced by the mesoscale convective weather and thunderstorms from below and exposed to solar photons from above. There has been great interest on the atmosphere‐ionosphere coupling, and numerous studies have been reported on the connection between thunderstorms and the ionosphere. However, the influence of thunderstorms on metallic species, which would significantly enhance our understanding of how Earth's atmosphere interacts with its ionosphere and studying the chemistry and physics of the MLT region, has rarely been studied. Here we present observational results on a statistical basis showing evidence that thunderstorm activities can affect the metal layer, by identifying a statistically significant enhancement of the neutral metal Na layer above thunderstorms at Haikou, China (20.0°N, 110.3°E). The thunderstorm‐generated gravity waves and electric field effects could be the mechanisms responsible for the lightning‐associated enhancement of Na layer. Key Points: It is the first observation of the enhanced mesospheric Na above thunderstorms The thunderstorm‐generated gravity waves and electric field effects could be responsible Thunderstorms affect the atmospheric/ionospheric chemistry and may be related to TLEs